Risālat al-Sheikh Asnāwī al-Quds al-Jāwī: Rebuttal of Jawi Ulama against Fatwa of the Meccan Ulama - Rohmana, Jajang A. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
This article is carried out to discuss the rebuttal of Jawi ulama, K.H. Raden Muḥammad Asnawi Kudus (1861-1959), against the fatwa of the muftī of Mecca, Sheikh ‘Abdullāh al-Zawāwī (1850-1925), in the early twentieth century. Asnawi’s rebuttal was written in an Arabic manuscript from Banyuwangi entitled Risālat al-Sheikh Asnawī al-Quds al-Jāwī and digitized by the DREAMSEA project DS 0042 00001. The pages contain rebuttal of Asnawi against al-Zawāwī’s fatwa regarding the legal status of reading hagiography or manāqib of Sheikh ‘Abd al-Qādir al-Jaylānī (1078-1166). The manuscript shows the initial response of traditionalist ulama of Jawi to the issue of modernist Islam discussed in the Malay-Indonesia archipelago. Asnawi strongly denied the Meccan muftī’s fatwa, which is influenced by the ideas of reformist-modernist Islam. This debate marks the dynamics of the social-intellectual environment of Muslims in Mecca and Southeast Asia in the early twentieth century.